1974
DOI: 10.3758/bf03333034
|View full text |Cite
|
Sign up to set email alerts
|

Stomach distention as a regulation of fluid intake

Abstract: Rats kept on a 23.5·h/day water-deprivation schedule were given 30 min access to four solutions, each on a separate test day, which were comprised of the factorial combination of two temperatures (12" and 31'C) and two NaCl concentrations (150 and 450 mOsm/kg). Food, which was available ad lib , and solution consumption measures were taken. More 31' C 150-mOsm/kg solution, which has the fastest stomach clearance rate of the four, was consumed than of the other three ; short-term and long-term food consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…This suggested that composition of the rehydration solution was not an important factor in determining initial fluid intake. Because the volumes drunk were similar to the reported capacity of the equine stomach (Pfeiffer and MacPherson 1990), satiation or cessation of drinking was probably a consequence of gastric filling, as described in rats (Engstrom and Deaux 1974). This suggestion is supported by the observation that the majority of initial drinking also occurred within the first minute after rehydration fluid was offered.…”
Section: Discussionsupporting
confidence: 59%
“…This suggested that composition of the rehydration solution was not an important factor in determining initial fluid intake. Because the volumes drunk were similar to the reported capacity of the equine stomach (Pfeiffer and MacPherson 1990), satiation or cessation of drinking was probably a consequence of gastric filling, as described in rats (Engstrom and Deaux 1974). This suggestion is supported by the observation that the majority of initial drinking also occurred within the first minute after rehydration fluid was offered.…”
Section: Discussionsupporting
confidence: 59%
“…The data appear in keeping with earlier postulations of a satiety mechanism separate from a correctional mechanism in thirst (O'Kelly, 1963), and consistent with the notion that gastric distention may constitute an important cuto()ff cue in the 23Yz-h water-<ieprivation schedule (Engstrom & Deaux, 1974;O'Kelly et aI., 1958).…”
Section: Discussionsupporting
confidence: 74%
“…If these micro behavioral changes in drinking reflect satiation, a possible contributing factor may well be gastric distention (Engstrom & Deaux, 1974;O'Kelly, 1954). In order to explore this possibility, the present study was designed to observe such microbehavior after preloads equal in volume, but differing in their capacity to quench thirst.…”
mentioning
confidence: 99%